2020
DOI: 10.1038/s41598-020-72491-9
|View full text |Cite
|
Sign up to set email alerts
|

Bardoxolone conjugation enables targeted protein degradation of BRD4

Abstract: Targeted protein degradation (TPD) has emerged as a powerful tool in drug discovery for the perturbation of protein levels using heterobifunctional small molecules. E3 ligase recruiters remain central to this process yet relatively few have been identified relative to the ~ 600 predicted human E3 ligases. While, initial recruiters have utilized non-covalent chemistry for protein binding, very recently covalent engagement to novel E3’s has proven fruitful in TPD application. Herein we demonstrate efficient prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 63 publications
(66 reference statements)
1
84
0
Order By: Relevance
“…Similarly, recent studies showed the discovery of new "ligandable" sites on RNF4 (Ward et al, 2019) and RNF114 ligases (Spradlin et al, 2019). The success of these E3 covalent highly reactive recruiters fostered the research toward covalent but reversible E3 ligase interactions, as shown for bardoxolone recruiting KEAP1 ligase (Tong et al, 2020).…”
Section: Challenges In Expanding the E3 Ligase Toolbox In Targeted Protein Degradationmentioning
confidence: 96%
“…Similarly, recent studies showed the discovery of new "ligandable" sites on RNF4 (Ward et al, 2019) and RNF114 ligases (Spradlin et al, 2019). The success of these E3 covalent highly reactive recruiters fostered the research toward covalent but reversible E3 ligase interactions, as shown for bardoxolone recruiting KEAP1 ligase (Tong et al, 2020).…”
Section: Challenges In Expanding the E3 Ligase Toolbox In Targeted Protein Degradationmentioning
confidence: 96%
“…To determine if RC E3REs could be used for TPD, Tong et al linked the natural product bardoxolone to JQ1. 101 Bardoxolone contains a reversible α-cyanoenone hetero-Michael acceptor that modifies the KEAP1 E3 ligase. PROTACs bearing a peptide that recruits KEAP1 were previously developed, demonstrating KEAP1 utility in TPD.…”
Section: Expanding Recruited E3 Ligasesmentioning
confidence: 99%
“…Despite this low level of engagement, the PROTACs induced substantial degradation of their targeted proteins. Following the early success seen with covalent PROTACs, the Nomura group incorporated bardoxolone, a reversible covalent binder of the E3 KEAP1, in a JQ1-bardoxolone PROTAC that afforded nanomolar BRD4 degradation ( 74 ). Nimbolide, a natural product extracted from neem leaves, which acts as a RNF114 E3 ligase recruiting ligand, has also been used to induce degradation of BRD4 and BCR-Abl when linked to JQ1 and dasatinib, respectively ( 75 , 76 ).…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%
“…To explore the role of cooperativity in ternary complex formation, the Ciulli group studied PROTAC-induced degradation of the BET protein family (BRD2, BRD3, BRD4) ( 83 ), a protein family extensively studied in the PROTAC field ( 27 , 60 , 73 , 74 , 81 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ). Using SPR and ITC, they found that ternary complexes with positive cooperativity (BRD4 BR2 :PROTAC MZ1:VHL; α = 22) caused more efficient cellular degradation than complexes with negative cooperativity (BRD4 BR2 :PROTAC MP61:VHL; α = 0.2).…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%